2022
DOI: 10.1111/os.13293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home‐based Telerehabilitation on the Postoperative Rehabilitation Outcome of Hip Fracture in the Aging Population

Abstract: Objective To investigate the effects of home‐based telerehabilitation based on the Internet‐based rehabilitation management system on hip function, activities of daily living and somatic integrative ability of elderly postoperative hip fracture patients. Methods From June 2020 to November 2020, we recruited 58 elderly postoperative hip fracture patients and randomly assigned them to the telephone group ( n = 29) and the telerehabilitation grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The study showed that HAT was feasible, safe, and effective for use in home-based rehabilitation of older adults after hip fractures. In the study conducted by Zhang et al, the effectiveness of telephone and telerehabilitation was compared [15]. They confirmed the improvement of functional recovery of hip fractures thus enhancing the ability to perform activities of daily living and somatic integration by the Internet-based rehabilitation management system applied to postoperative home rehabilitation of hip fractures [15].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 87%
See 1 more Smart Citation
“…The study showed that HAT was feasible, safe, and effective for use in home-based rehabilitation of older adults after hip fractures. In the study conducted by Zhang et al, the effectiveness of telephone and telerehabilitation was compared [15]. They confirmed the improvement of functional recovery of hip fractures thus enhancing the ability to perform activities of daily living and somatic integration by the Internet-based rehabilitation management system applied to postoperative home rehabilitation of hip fractures [15].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 87%
“…In the study conducted by Zhang et al, the effectiveness of telephone and telerehabilitation was compared [15]. They confirmed the improvement of functional recovery of hip fractures thus enhancing the ability to perform activities of daily living and somatic integration by the Internet-based rehabilitation management system applied to postoperative home rehabilitation of hip fractures [15]. Another study comparing the efficacy of telephone and telerehabilitation groups is by Wu et al [16].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 89%
“…Our research group has developed the family‐oriented postoperative rehabilitation management system for geriatric hip fracture (referred to as the “rehabilitation management system”). In our previous study 14 we had proved that this system can enhance the ability to perform activities of daily living and somatic integration in the postoperative rehabilitation of hip fracture patients. However, in the operation of hip fracture, total hip arthroplasty has longer operation time and more blood loss, which is easy to cause postoperative complications.…”
Section: Introductionmentioning
confidence: 97%
“…This experiment not only focuses on the rehabilitation of limb function but also on the psychological function and postoperative complications of patients. On the basis of our previous study, 14 we increased the follow‐up time to reflect the rehabilitation effect for a longer time. The following were the aims of this: (i) to investigate the therapeutic effect of home‐based telerehabilitation on postoperative hip function and functional independence; (ii) to determine whether home‐based telerehabilitation can effectively relieve psychological anxiety; and (iii) to analyze the effect of rehabilitation management system on preventing postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Despite the existence of evidence supporting the use of digital tools after hip surgery, [26][27][28][29] to the best of our knowledge, there are just a few mHealth interventions for this population. [30][31][32][33][34] It is important to develop new mHealth interventions to provide a comprehensive tele-rehabilitation program, focussing not only on rehabilitation but also on secondary fracture prevention. Thus, we developed the ActiveHip+ mHealth system as an alternative for those older adults who cannot access to in-person rehabilitation.…”
Section: Introductionmentioning
confidence: 99%